Stability of spatial interpolation functions in finite element one-dimensional kinematic wave rainfall-runoff models - Anh, Luong Tuan; Larsson, Rolf (VNU Journal of Science: Earth and Environmental Sciences; Vol 24 No 2, 2008)
Abstract